Capacity building approaches to emergency management in rural communities: recommendations from survivors of the British Columbia Wildfires, 2003. (8th June 2007) - Cox, Robin S.
This paper responds to the ongoing calls within emergency management for more community-driven and capacity building approaches to the response to and recovery from natural disasters. Moving from the rhetoric of community-driven approaches to the practice, this paper highlights and draws on specific practice recommendations made by residents in two rural Canadian communities affected by a devastating forest fire. The recommendations made by the survivors of the McLure Fire, in British Columbia, Canada, provide a concrete framework for engaging with rural communities in developing emergency management practices that are more relevant to and congruent with the unique challenges and strengths of their communities.